Mindfulness-Based Intervention Kurang Efektif untuk Menurunkan Maladaptive Perfectionism dan Self-Criticism: Sebuah Meta Analisis - Livia Tanujaya; Ananta Yudiarso (Humanitas (Jurnal Psikologi), 2024)
The same characterization found in maladaptive perfectionism and self-criticism, namely target-oriented and self-judgment when the target is not achieved. Both are also associated with stress, anxiety and depressive symptoms and are therefore seen as negative. This meta-analysis study conducted using secondary data through previous studies that were reviewed with the aim of seeing the effectiveness of mindfulness-based interventions to reduce maladaptive perfectionism and self-criticism. A total of 10 articles were selected for the meta-analysis, which were selected based on inclusion and exclusion criteria. Participants varied from primary and secondary school students, and adults (18 years or above) with various characteristics, such as college students and patients. This research resulted in mindfulness interventions being less effective for reducing maladaptive perfectionism and self-criticism, with possibilities for further research with moderators or more research involved in the future.